Use of portable devices and an innovative and non-destructive index for in-field monitoring of olive fruit ripeness - Cinosa, Nicola; Portarena, Silvia; Almandi, Leen; Berrettini, Annalisa; Torres, Myriam Mariela; Pierantozzi, Pierluigi; Villa, Paola; Galletti, Andrea; Famiani, Franco; Farinelli, Daniela (MDPI, 2023)
A new non-destructive index of absorbance difference (IAD), calculated with different wavelengths as references, near the chlorophyll absorbance peak or that for anthocyanin, has been used to determine the fruit ripening of several fruit species using portable devices such as Standard DA-Meter® and Kiwi-Meter®. In this study, for the first time, the application of the IAD was evaluated on single, intact olives of the Leccino cultivar, as a single non-destructivematurity index to follow ripening in the field, directly on the tree. The IAD determined by both devices was found to be useful for monitoring the olive ripening, however, better performance was achieved with the Kiwi-Meter®. In fact, the IAD determined by this device wasmore effective atmeasuring all the studied olive ripening parameters in the calibration and validation datasets with acceptable accuracy. Specifically, better performance of the IDA by Kiwi-Meter® was observed in estimation of the color index (R2 = 0.817, DRMSEC = 0.404 and RPIQ = 3.863 for calibration and R2 = 0.752, DRMSECV = 0.574 and RPIQ = 3.244 for validation), confirming its potential for evaluating the degree of olive ripeness. This novel index has significant applicative possibilities, since it would allow rapid, on-site screening of the best harvesting time to improve the olive production in terms of both yield and quality.